2001
DOI: 10.1038/sj.ijo.0801905
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiology of food preferences

Abstract: Investigations with laboratory animals can reveal much about the basic psychobiological determinants of food preference and diet-induced overeating. When offered a choice of foods, rats typically prefer high-fat and=or high-sugar food items over their nutritionally balanced chow diet. In addition, they may increase their total energy intake by 20 -40% and consequently develop mild to moderate obesity. The role of flavor and postingestive nutritional actions on the preference for and overconsumption of fat-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 16 publications
3
39
0
1
Order By: Relevance
“…A greater daily caloric intake from the HF diet was observed in both the control (90.4%) and JTT-130 (90.2%) groups, with no differences observed between the two groups (Table 2 and Figures 2 and 3(a)). This higher preference for the HF diet in our experiment was consistent with the previous report wherein rats were shown to have a higher preference for fatty diets [19, 20]. …”
Section: Resultssupporting
confidence: 93%
“…A greater daily caloric intake from the HF diet was observed in both the control (90.4%) and JTT-130 (90.2%) groups, with no differences observed between the two groups (Table 2 and Figures 2 and 3(a)). This higher preference for the HF diet in our experiment was consistent with the previous report wherein rats were shown to have a higher preference for fatty diets [19, 20]. …”
Section: Resultssupporting
confidence: 93%
“…The strongest associations between hedonic ratings and consumption were for foods high in energy density, aligning well with population-based studies that have reported that high calorie foods are most preferred (Gibson & Wardle, 2003). Previous experimental work in laboratory animals and in children has further confirmed that foods of high energy content become preferred over those that have fewer calories (Johnson, McPhee, & Birch, 1991; Kern, McPhee, Fisher, Johnson, & Birch, 1993; Sclafani, 2001). …”
Section: Discussionmentioning
confidence: 90%
“…The need for an energy-rich diet may have also shaped our ability to detect and metabolize high-fat foods. We show strong preferences for lipidrich foods that are based on the smell, texture, and taste of fatty foods, [24][25][26] and our brain has the ability to estimate the energy content of foods. 27 We have acquired an enhanced capacity to digest and metabolize higher fat diets.…”
Section: Evolution and Diversificationmentioning
confidence: 96%